2017
DOI: 10.1002/adem.201600842
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Ductility Balance on an Extruded Mg–Zn–Ca–La Alloy

Abstract: Mg-6Zn-0.7Ca-0.2La (wt%) alloy is cast and extruded in the present study. The microstructure of the as-extruded Mg-6Zn-0.7Ca-0.2La (wt%) alloy is investigated via scanning electron microscopy (SEM), transmission electron microscope (TEM) and electron backscattering diffraction (EBSD). Results show that the as-extruded Mg-6Zn-0.7Ca-0.2La (wt%) alloy exhibited a balanced strength and ductility with the yield strength of 261 MPa and elongation-to-fracture of 20.7%. The superior strength is mainly attributed to gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
2
2
Order By: Relevance
“…The gauge length is 15 mm and cross sectional area is 6 Â 2 mm. In our previous investigations, [23] a good combined balance on mechanical properties of an extruded Mg-Zn-Ca-La alloy with the elongation-to-fracture of the as-extruded Mg-Zn-Ca-La alloy was only about 21%, which is much lower than that of the peakaged Mg-Zn-Ce alloy in the present study. During the initial stages of ageing, the hardness increased slightly.…”
Section: Methodscontrasting
confidence: 51%
See 1 more Smart Citation
“…The gauge length is 15 mm and cross sectional area is 6 Â 2 mm. In our previous investigations, [23] a good combined balance on mechanical properties of an extruded Mg-Zn-Ca-La alloy with the elongation-to-fracture of the as-extruded Mg-Zn-Ca-La alloy was only about 21%, which is much lower than that of the peakaged Mg-Zn-Ce alloy in the present study. During the initial stages of ageing, the hardness increased slightly.…”
Section: Methodscontrasting
confidence: 51%
“…Meanwhile, the elongation-to-fracture of the peak-aged alloys was retained up to 30%. In our previous investigations, [23] a good combined balance on mechanical properties of an extruded Mg-Zn-Ca-La alloy with the elongation-to-fracture of the as-extruded Mg-Zn-Ca-La alloy was only about 21%, which is much lower than that of the peakaged Mg-Zn-Ce alloy in the present study. Figure 3 compared the yield strength versus elongation to fracture between the Mg-Zn-Ce alloy in the present study and commercial Mg alloys, [24] as well as GW (Mg-Gd-Y) series alloys.…”
Section: Methodscontrasting
confidence: 51%
“…Magnesium (Mg) alloys, the lightest metal structural material in the industry, have been widely used in transportation, electronics, military, and other industries. [1][2][3][4] Among them, the development of magnesium alloys is closely tied to the solution of emission problems in the transportation field. [5][6][7] Improving the mechanical properties of magnesium alloys through plastic deformation technology has become an important approach for engineering application of magnesium alloys.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that enhanced deep draw ability of ZE10 alloy, reduced serrated cracking of AZ31 alloy, improved formability and ductility of Mg–Ca–Zr alloy were obtained after their texture was weakened. Balanced strength and ductility of Mg–Zn–Ca–La alloy was realized with texture modification . The methods aimed at modifying texture are based either on optimization of deformation mechanism or on interfering the dynamic recrystallization (DRX) process.…”
mentioning
confidence: 99%